Effect of operational and water quality parameters on conventional ozonation and the advanced oxidation process O3/H2O2: Kinetics of micropollutant abatement, transformation product and bromate formation in a surface water. (1st October 2017) - Bourgin, Marc; Borowska, Ewa; Helbing, Jakob; Hollender, Juliane; Kaiser, Hans-Peter; Kienle, Cornelia; McArdell, Christa S.; Simon, Eszter; von Gunten, Urs
Abstract: The efficiency of ozone-based processes under various conditions was studied for the treatment of a surface water (Lake Zürich water, Switzerland) spiked with 19 micropollutants (pharmaceuticals, pesticides, industrial chemical, X-ray contrast medium, sweetener) each at 1 μg L −1 . Two pilot-scale ozonation reactors (4–5 m 3 h −1 ), a 4-chamber reactor and a tubular reactor, were investigated by either conventional ozonation and/or the advanced oxidation process (AOP) O3 /H2 O2 . The effects of selected operational parameters, such as ozone dose (0.5–3 mg L −1 ) and H2 O2 dose (O3 :H2 O2 = 1:3–3:1 (mass ratio)), and selected water quality parameters, such as pH (6.5–8.5) and initial bromide concentration (15–200 μg L −1 ), on micropollutant abatement and bromate formation were investigated. Under the studied conditions, compounds with high second-order rate constants k O3 >10 4 M −1 s −1 for their reaction with ozone were well abated (>90%) even for the lowest ozone dose of 0.5 mg L −1 . Conversely, the abatement efficiency of sucralose, which only reacts with hydroxyl radicals (OH), varied between 19 and 90%. Generally, the abatement efficiency increased with higher ozone doses and higher pH and lower bromide concentrations. H2 O2 addition accelerated the ozone conversion to OH, which enables a faster abatement of ozone-resistant micropollutants. Interestingly, the abatement of micropollutants decreased with higher bromide concentrations during conventional ozonation due to competitive ozone-consuming reactions, except for lamotrigine, due to the suspected reaction of HOBr/OBr − with the primary amine moieties. In addition to the abatement of micropollutants, the evolution of the two main transformation products (TPs) of hydrochlorothiazide (HCTZ) and tramadol (TRA), chlorothiazide (CTZ) and tramadol N -oxide (TRA-NOX), respectively, was assessed by chemical analysis and kinetic modeling. Both selected TPs were quickly formed initially to reach a maximum concentration followed by a decrease of their concentrations for longer contact times. For the studied conditions, the TP's concentrations at the outlet of the reactors ranged from 0 to 61% of the initial parent compound concentration, CTZ being a more persistent TP against further oxidation than TRA-NOX. Finally, it was demonstrated in both reactors that the formation of bromate (BrO3 − ), a potentially carcinogenic oxidation by-product, could be controlled by H2 O2 addition with a general improvement on micropollutant abatement. Post-treatment by granular activated carbon (GAC) filtration enabled the reduction of micropollutants and TPs concentrations but no changes in bromate were observed. The combined algae assay showed that water quality was significantly improved after oxidation and GAC post-treatment, driven by the abatement of the spiked pesticides (diuron and atrazine). Graphical abstract: Highlights: The abatement of 19 micropollutants was studied by ozonation and the AOP O3 /H2 O2 . The effects of O3 /H2 O2 and bromide doses and pH were investigated in two reactors. Micropollutant abatement was generally higher in the AOP compared to ozone. The yield of two monitored transformation products ranged from 0–61%. Bromate formation was significantly mitigated in presence of H2 O2 .